Behavior of Islamic Community Development Students 3 A towards Clash of Champions in Ruangguru on Youtube - Damayanti, Lisna; Azizah, Adhiya Nur; Naftali, Muhammad Lazuardi; Rizki, Muhammad; Nisa, Pia Khoirotun (Journal of Social Science and Education Research, 2025)
The development of digital technology has brought great changes in the world of education, especially in developing countries such as Indonesia. One solution that overcomes limited access to education is an online learning platform such as Ruangguru. This study aims to analyze the behavior of students of the Islamic Community Development Study Program (PMI) 3A towards the Clash of Champions (COC) show organized by Ruangguru on the YouTube platform, focusing on its impact on adolescent behavior patterns and learning styles. The method used is a qualitative approach with data collection techniques through interviews, observations, and documentation. The results show that there is a variation in student involvement, which is influenced by their learning interests and preferences. Some students are actively engaged, developing critical thinking and collaboration skills, while others watch the show passively. This study provides recommendations to maximize the use of COC impressions in education by involving the role of teachers and utilizing social media to expand the reach of educational content.